The models of behaviour ofthe old generation historians in the presence of sovietization process - Švedas, Aurimas (Lietuvos istorijos studijos, 2008)
Ever since Lithuania has restored its independence in 1990, wide-ranging debates have been taking place on a question of individual and societal conformance, resistance, and collaboration during the times of Soviet occupation. This article inquires into strategies and tactics of behavior that the most famous historians of independent Lithuania have chosen to pursue in the presence of existential and professional challenges made by the Soviet occupation and its totalitarian system. The older generation of historians from independent Lithuania was deliberately isolated during the time of creating the Soviet model of history; their influence was limited as these scholars were directed to the "ideologically safe" spheres of work and were prevented from reading "complicated courses" to students. Historians with the "bourgeois past" were closely watched and some of them even came under the real threat of repressions. At the same time, authors and stewards of the Soviet model of history cynically attempted to use the authority of the historians of independent Lithuania by constantly assigning them tasks of conjuncture.While facing existential and professional challenges, the old generation of Lithuanian historians had to choose from three, often contradictory, strategies of behavior: First path was to separate themselves from the perversions of the Soviet reality by refusing to participate in joint projects and by assuming an apolitical attitude.Second path was, consciously or not, to constantly seek to create controversy in the official Soviet discourse of history, while bringing upon themselves disgrace from the history stewards.Third approach was to attempt to escape from the schemes and to correct the general constructs of Lithuanian history by influencing Soviet historiography with the usage of correct propositions and carefully chosen quotes from the Marxist-Leninist classics.As the sovietization process was leaping forward, making a choice among resistance, conformance, and collaboration became an existential and professional challenge, which the elite of the interwar community of historians had to face every day.
Keywords: -